Is ESWL Score a Good Predictor of Stone Clearance? A Comparison in Patients Undergoing ESWL With Stones of Low, Medium, and High Density - Khan, Muhammad Ahsan Rehman; Mithani, Shoaib; Fareed, Wajahat (Biological and Clinical Sciences Research Journal, 2025)
Extracorporeal shock wave lithotripsy (ESWL) remains a first-line, non-invasive treatment for renal stones. However, predicting treatment success remains a challenge. The ESWL Score was proposed as a simple predictive tool, yet its real-world validation in prospective settings remains limited. Objective: To assess the predictive capabilities of the ESWL Score in determining stone clearance following ESWL in a prospective clinical setting. Methods: A prospective observational study was conducted at The Kidney Centre, Karachi, from October 2024 to April 2025. All eligible patients undergoing ESWL for renal calculi were enrolled. Demographic data, including age, gender, height, and weight, were recorded, and body mass index (BMI) was calculated. Stone characteristics—size, location, number, and density—were assessed via non-contrast computed tomography (NCCT). The ESWL Score was calculated for each patient. Stone clearance was assessed one week post-procedure using plain X-ray KUB, with clearance defined as no visible fragments or residual fragments <4 mm. Statistical analysis was performed using IBM SPSS version 26. Logistic regression was used to evaluate the predictive value of the ESWL Score. Results: A total of 143 patients were included, with a median age of 43 years (IQR=20); 87 (60.8%) were male. Median stone size was 8.1 mm (IQR=3.9), ranging from 4.3 to 15.5 mm. Median stone density was 890 HU (IQR=366), and median BMI was 24.4 kg/m² (IQR=2.6). Most patients fell within normal or overweight BMI categories. Successful stone clearance was achieved in 112 (78.3%) patients. The most common ESWL Score was 2 (45.5%), followed by 3 (36.4%). Stone size significantly affected clearance outcomes (p<0.05), whereas BMI and stone density did not. Logistic regression analysis revealed that the ESWL Score was a significant predictor of stone clearance. Specifically, patients with an ESWL Score of 2 had 9.54 times higher odds of successful clearance (p<0.001). Conclusion: The ESWL Score is a practical and reliable tool for predicting treatment success in patients undergoing ESWL for renal stones. Its simplicity and predictive validity make it a valuable adjunct in pre-procedural planning.